PENGARUH METODE MIND MAPPING DALAM MENULIS KARANGAN PADA MAHASISWA ANGKATAN 2021 PRODI PENDIDIKAN BAHASA JEPANG - Aisyah, Dinda; Rahayu, Nana; Yohani, Adhisti Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: In learning activities, a method is needed to increase student creativity, one of which is the Mind Mapping method.  This research aims to find out how to apply the mind mapping method to increase creativity in sakubun learning in the Nihongo Koutou Happyou 2 course for students in the class of 2021 of the Japanese Language Education Study Program, FKIP, Riau University.  This research was carried out by observing in the field with a total of 25 students.  Data collection is carried out through the results of learning activities by creating a mind map.  The results of the research show that the mind mapping method can increase student creativity in learning sakubun in the nihongo koutou happyou 2 course. Keywords: Mind Mapping, Sakubun , Activities